Pengaruh Terapi Benson Terhadap Tingkat Penurunan Nyeri Pada Pasien Post Operasi Transurethral Resection of The Prostate di RSI Purwokerto - Rettob, Cicilia Dei; Firdaus, Eza Kemal; Yanti, Linda (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Benign prostatic hyperplasia (BPH) is a common condition in elderly men that often causes lower urinary tract symptoms. (LUTS). In men aged 60 to 90 years, the histological prevalence of BPH is 50 to 80%.The type of this research is experimental research using a pre-experimental design with a One group pretest posttest design. In this study, all BPH patients who underwent TURP surgery, totaling 30 patients, were included. It can be observed that the highest age group is 50-59 years with 11 respondents (36.7%) and the lowest is the 80-89 years age group with 3 respondents (10.0%). The highest level of education was junior high school, with 11 respondents (36.7%), and the lowest was higher education, with 4 respondents (13.3%). Previous surgical history was present in 19 respondents (63.3%) and absent in 11 respondents (36.7%). It can be observed that the highest condition before Benson therapy was a pain level of 4-6 (moderate pain) in 30 respondents (100%). Whereas it can be observed that the highest level of pain after Benson therapy was 1-3 (mild pain) in 29 respondents (96.7%) and the lowest level was 4-6 (moderate pain) in 1 respondent (3.3%).According to the Wilcoxon test results, a p-value of 0.05 means H0 is rejected and Ha is accepted, which is interpreted as a significant effect of Benson therapy on the level of pain reduction before and after the administration of Benson therapy. This shows that there is an effect of Benson therapy, evident in the 4-6 category (moderate pain) during the pre-treatment (before) phase, which changed to the 1-3 category (mild pain) and the 4-6 category (moderate pain) during the post-treatment (after) phase.